Individual and experiential predictors of character development across the deployment cycle. Issue 4 (July 2022) - Chopik, William J; Kelley, Whitney L; Vie, Loryana L; Lester, Paul B; Bonett, Douglas G; Lucas, Richard E; Seligman, Martin EP
How soldiers adapt to and change in response to the deployment experience has received a great deal of attention. What predicts which soldiers are resilient and which soldiers decline in character strengths across the deployment transition? We examined this question in two analyses drawing from the same data source of soldiers deploying for the first time (Analysis 1: N = 179, 026; Analysis 2: N = 85, 285; Mage = 24.6–24.7 years old, SD = 4.87; 66.5–66.9% White). Specifically, we examined how individual (e.g. sociodemographic, military) and deployment (e.g. stressful experiences) characteristics predict character development across the deployment cycle. Character strengths were assessed once before and up to three times after soldiers' return from deployment. Reproducing previous work, we found evidence for two classes of change—a resilient class ("stable high") and a recovery class ("persistent low"). The strongest predictor of high, resilient character strength levels was better self-rated health at baseline. The findings are discussed in the context of the mechanisms that drive character development, evidence for post-traumatic growth, and practical implications for the U.S. Army.